Manajemen Risiko Pada Bandara Soekarno Hatta Berbasis ISO 31000 - Terry George Abisay; N Nurhadi (Jurnal Teknik Industri, 2013)
Soekarna Hatta Airport as an international aviation company hasn’t yet implemented an international standard risk management system based on ISO 31000, so it triggers the occurrence of negative impacts to the human, environment, property and company reputation. This research aims to conduct a risk assessment and control by using an international standard risk management system. Risk management research is focused on the negative impacts caused by an event of airport operations, particularly operations facility and machine. The Stages of the risk management process are based on ISO 31000 including risk identification, risk analysis, and risk evaluation using fishbone and Risk Breakdown Structure (RBS) tool. Impact Expectations and possible occurrence are mapped through the risk matrix which is defined by the Federation Aviation Administration (FAA). The results showed that there were7 events at Soekarno Hatta airport that have potential risk, namely, outbreak of the runway track, plane accidence during take-off/landing, disruption of flight navigation and communication services, accidence in the apron area, security disruption at the airport, aircraft jetblast, and entry of dangerous goods on board.